More iPhone cool projects : cool developers reveal the details of their cooler iPhone apps and discuss their iPad development experiences - Chin, Danton (New York : Apress, 2010)
Provides information on creating applications for the iPhone.
Using concurrency to improve the responsiveness of iPhone and iPad applications / Danton Chin -- Your own content pipeline, importing 3D art assets into your iPhone game / Claus Hofele -- How FlightTrack uses external data providers to power this best-selling travel app / Ben Kazez Write better code and save time with unit testing / Saul Mora, Jr. -- Fun with computer vision, face recognition with OpenCV on the iPhone / Leon Palm -- How to use OpenGL fonts without losing your mind / Scott Penberthy -- Game development with Unity / Ben Britten Smith -- Cocos2d for iPhone and iPad, it is easier than you think / Chuck Smith -- Creating an audio-centric app for the iPhone with AVAudioPlayer / David Smith -- Implementing push notifications at eBuddy / Joost van de Wijgerd & Arne de Vries.
Includes bibliographical references and index.
Keywords: iPhone (Smartphone) -- Programming; Mobile computing; Application software -- Development